2013
DOI: 10.4067/s0717-73562013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Precolumbian Raw-Material Exploitation in Southern Peru-Structures and Perspectives

Abstract: The article deals with the exploitation of raw materials during pre-colonial times in Southern Peru especially pre-Columbian mining and quarrying activities in the valleys of Palpa and Nasca. Between 2006 and 2009 the Peruvian-German Palpa-project has discovered several places related to the extraction and the processing of lithic material, ores and minerals. All places detected so far are locations with traces of small scale mining. The available evidence demonstrates that production of raw materials has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Geochemical characterization by neutron activation analysis (NAA) and X-ray fluorescence (XRF) analysis of obsidian artifacts and geological reference samples demonstrated that the obsidian raw material used by Paracas people in the northern Nasca Drainage was obtained almost exclusively (93%) from the Quispisisa source, and more precisely its Jichja Parco outcrop, in the high-altitude puna of the Ayacucho Region (Gräfingholt 2016; Reindel et al 2013; Stöllner et al 2013). Quispisisa/Jichja Parco was one of the most significant mines in the prehispanic central Andes, as evidenced by the extensive distribution of its obsidian over distances up to 1,000 km (Burger and Glascock 2000; Matsumoto et al 2018; Tripcevich and Contreras 2011, 2013).…”
Section: The Paracas Economy: Archaeological Evidence From the Northe...mentioning
confidence: 99%
“…Geochemical characterization by neutron activation analysis (NAA) and X-ray fluorescence (XRF) analysis of obsidian artifacts and geological reference samples demonstrated that the obsidian raw material used by Paracas people in the northern Nasca Drainage was obtained almost exclusively (93%) from the Quispisisa source, and more precisely its Jichja Parco outcrop, in the high-altitude puna of the Ayacucho Region (Gräfingholt 2016; Reindel et al 2013; Stöllner et al 2013). Quispisisa/Jichja Parco was one of the most significant mines in the prehispanic central Andes, as evidenced by the extensive distribution of its obsidian over distances up to 1,000 km (Burger and Glascock 2000; Matsumoto et al 2018; Tripcevich and Contreras 2011, 2013).…”
Section: The Paracas Economy: Archaeological Evidence From the Northe...mentioning
confidence: 99%
“…En efecto, en las zonas de Ica, Palpa y Nasca se han identificado una serie de minas prehistóricas de óxido de hierro y de cobre que estuvieron en explotación al menos desde el período Intermedio Temprano hasta momentos prehispánicos tardíos (Vaughn et al 2007(Vaughn et al , 2013a(Vaughn et al y 2013bEerkens et al 2009;Stöllner et al 2013;Van Gijseghem et al 2011. A excepción de la Mina Primavera, sin embargo, y tal como sucede con las minas conocidas para la costa norte del Perú, casi todos los sitios mineros identificados en el área Nasca aún están a la espera de investigaciones y descripciones más sistemáticas.…”
Section: La Minería Prehispánicaunclassified
“…En consecuencia, cabe mencionar que la presencia imperial en Inca Viejo podría explicarse, en parte, por el valor otorgado a este mineral. Se debe considerar que existe escasa información acerca de fuentes de turquesa en el territorio peruano, el corazón del Imperio inca (Stöllner et al 2013). Por el contrario, en el sector surandino, se reconocen varias minas de este recurso, especialmente en el norte de Chile, en concordancia con la diversidad de martillos señalada previamente (Figueroa et al 2013;González y Westfall 2008;González et al 2017;Núñez 1999;Núñez et al 2003;Salazar y Vilches 2014;Salazar et al 2013).…”
Section: Introductionunclassified